Expression and maturation of human foamy virus Gag precursor polypeptides. - Giron, M L (1997)
In this report, we address the processing of the Gag polypeptides of human foamy virus previously reported to be atypical. In the cytoplasm or the nucleus of infected cells as well as in free virus particles, two Gag precursor polypeptides were identified at approximately 72 and 68 kDa, p72 giving rise to p68 by a maturation process. Efficient maturation of Gag precursors was observed only in two situations: (i) during the early steps of virus adsorption and (ii) under experimental conditions, including treatment with DNase I, known to dissociate actin polymers associated with high ionic strength and ionic detergents. Rather than being a defective viral protease function, an association of Gag precursors with a cytoskeleton network might be responsible for the low rate of Gag protein maturation through inhibition of their cleavage by the protease.